Quality Analysis of JAKLITERA Website with Webqual 4.0 Method and Importance-Performance Analysis - Abilawa, Rakai; Nurmawati, Erna (Jurusan Informatika Universitas Tanjungpura, 2024)
Public libraries must develop a library service system based on information and communication technology. In an effort to realize this, the Jakarta Library launched the JAKLITERA website which is an integrated library website to facilitate borrowing library collections anywhere and anytime. To achieve this goal, it is necessary to pay attention to the quality of the website, because it will be a reflection of the library's services. Good website quality will have an impact on user satisfaction in visiting the website. To measure, the right method is needed according to the purpose of assessing website quality. Webqual 4.0 method is considered appropriate to use because basically the quality measurement technique with this method takes user perception as a basis. The analysis used to determine indicators/attributes that need to be improved or have met user expectations and website quality is IPA and gap analysis, while the CFA method will be used to see indicators that contribute less. Based on the results of gap analysis and IPA, there are 21 indicators with negative values and 4 indicators that are prioritized for improvement, while the CFA results show that there is 1 indicator that is categorized as less contributing to the JAKLITERA website.